Three-dimensional multi-dimensional colorful light-transmitting ceramic tile and preparation process thereof

Through three-dimensional multi-dimensional design and multi-layer process, combined with concave and convex molds and reverse positioning printing, the limitations of color and optical effects of colored flower stone imitation tiles are solved, and artistic effect and stability similar to natural colored flower stones are achieved.

CN119260891APending Publication Date: 2025-01-07QINGYUAN GANI CERAMICS CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411378114.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing colored flower stone imitation tiles have significant limitations in color transparency, natural gradient, layering and optical effects, and it is difficult to simulate the beauty of natural colored flower stone.

Method used

Adopt three-dimensional colorful flower transparent ceramic tiles design, through the combination of colorful rough blanks, colored grain layers, protective glaze layers and positioning printing layers, combining concave and convex mold pressing, scanning stone, drying, printing, spraying dry particles and reverse positioning Printing process simulates the texture and patterns of natural colored flower stones to achieve precise color transparency and natural gradient.

Benefits of technology

It realizes the delicate layering and rich optical effects on the surface of the tiles, achieves an artistic effect comparable to natural colored flower stones, and simplifies the production process and improves the firmness of the pattern and the stability of the color.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260891A_ABST
    Figure CN119260891A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic tiles, in particular to a three-dimensional multi-dimensional colorful light-transmitting ceramic tile and a preparation process thereof. The ceramic tile comprises a colorful rough blank, a pattern layer, a colored crystal grain layer and a protective glaze layer are sequentially arranged on the surface of the blank from bottom to top, and a positioning printing layer is arranged on the bottom face of the blank. Different color layers are designed on the surface and the bottom surface of the colorful rough blank by simulating the texture and the pattern of the natural colored flower stone, and fixed-point colored crystal grains are combined with different layers of pattern layers, glaze layers and the like through multi-layer design, so that accurate color transparency and natural gradual change can be realized to construct a fine layering sense and a rich optical effect; the artistic effect comparable with that of natural colored flower stone is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, and in particular to a three-dimensional multi-dimensional colorful light-transmitting ceramic tile and a preparation process thereof. Background Art

[0002] Colored marble, as a natural colored stone with texture, is known as the "No. 1 ornamental stone in the world" for its unique formation process and excellent decorative value. It has a very high status in the field of high-end architectural decoration. However, the mining, processing and transportation costs of natural colored marble are high, making it difficult to use in daily life. The production of traditional imitation colored marble tiles mainly relies on surface decoration technologies such as screen printing, inkjet printing, three-dimensional fabrics, dry and wet fabrics, etc. Although these processes can imitate the appearance of colored marble to a certain extent, they only imitate the color appearance surface, and the actual product "shape" is not "spirit". Moreover, the chemical reaction of pigments during the high-temperature firing of colored glazes causes a large change in color depth, lacks a sense of transparency, and is difficult to show the beauty of the light transmittance of colored marble; the single use of multiple screens and concave and convex rubbing methods is rigid in color control and three-dimensional color changes, and the color gradient and detail expression appear mechanical and lack natural flow. At present, the imitation of colored marble still has significant limitations in terms of the natural gradient of brick surface color, surface layering and optical effects. Summary of the invention

[0003] In order to overcome these limitations, the present application provides a three-dimensional, multi-dimensional, colorful, translucent ceramic tile and its preparation process, which can not only achieve precise color transparency and natural gradient, but also construct a delicate sense of layering and rich optical effects on the surface of the ceramic tile, achieving an artistic effect comparable to that of natural colorful stone.

[0004] The technical solution adopted by this application to solve its technical problem is:

[0005] In the first aspect, the present application provides a three-dimensional multi-dimensional colorful translucent ceramic tile, comprising a colorful rough blank, the surface of which is provided with a pattern layer, a colored grain layer, and a protective glaze layer in sequence from bottom to top, and a positioning printing layer is provided at the bottom of the blank; the colorful rough blank is formed by pressing a translucent blank and a translucent colorant through a concave and convex mold; the colored grain layer is distributed in the colorful part of the tile.

[0006] By simulating the texture and pattern of natural colored stone, different color layers are designed on the surface and bottom of the colorful rough blank. The multi-level design combines fixed colored grains with different levels of pattern layers, glaze layers, etc., to achieve precise color transparency and natural gradient, construct a delicate sense of layering and rich optical effects, and achieve an artistic effect comparable to natural colored stone.

[0007] In a second aspect, the present application provides a preparation process of the above-mentioned three-dimensional multi-dimensional colored light-transmitting ceramic tiles, comprising the steps of:

[0008] S1: Scan the stone and make a concave and convex mold;

[0009] S2: Using a concave-convex mold, the light-transmitting blank and the light-transmitting colorant are pressed to form a colorful rough blank;

[0010] S3: drying, printing a decorative pattern on the surface of the dried blank to form a pattern layer;

[0011] S4: adding colored grains locally on the surface of the blank obtained in step S3, wherein the colored grains correspond to the colored patterned parts of the blank;

[0012] S5: spraying dry granular protective glaze on the surface of the body obtained in step S4;

[0013] S6: firing, polishing;

[0014] S7: Process the bottom of the tile obtained in step S6, and then print the decorative pattern described in step S3 on the bottom of the tile in reverse positioning.

[0015] Preferably, in the step S1, the three-dimensional effect of the colored flower part is extracted by light and shade processing to enhance the three-dimensional effect of the colored flower.

[0016] Preferably, in step S2, the overall light transmittance of the light-transmitting blank and the colorant is ≥5%, and the colorant is a wrapped colorant.

[0017] Preferably, in step S4, colored grains are locally added to the surface of the blank by screen printing, which allows for more precise positioning and better control of the amount of glazing of the grains, so as to facilitate control in combination with the thickness of the concave and convex texture of the tile, thereby achieving a better three-dimensional effect on the surface of the final tile.

[0018] Preferably, in step S7, processing the bottom of the tile includes: performing surface plasma cleaning on the bottom of the tile, and then providing a nano-silicon dioxide layer. After such processing, the bottom pattern is not easy to fall off and has a good visual effect.

[0019] Preferably, in step S7, a pattern is printed on the bottom of the treated tile using UV ink, which can be quickly cured and has rich colors, achieving precise color matching and gradient effects, and further enhancing the light and dark difference to achieve a sense of stone transparency.

[0020] Further preferably, in step S7, the UV printing ink comprises printing ink and solid powder, the solid powder comprises color powder and glaze powder, and the chemical composition of the glaze powder, in terms of oxide mass percentage, comprises: SiO2 45-50%, Al2O3 18-23%, CaO 8-13%, MgO 2-3.5%, K2O 0.5-1%, Na2O4-5%, BaO 0.3-0.5%, ZnO2-3% and the remainder on ignition.

[0021] Further preferably, in step S7, the solid powder in the rose red UV ink is composed of the following components by mass: 100 parts of glaze powder, 1.5 parts of chromium oxide, 4.0 parts of tin oxide, 1.2 parts of ferric oxide, and 0.3 parts of cobalt oxide;

[0022] The solid powder in the pink UV ink is composed of the following components by mass: 100 parts of glaze powder, 5.0 parts of tin oxide, 2.5 parts of spodumene, 0.2 parts of cobalt oxide, and 1.0 parts of aluminum oxide;

[0023] The solid matter in the yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 3.0 parts of cerium oxide, and 0.8 parts of ferric oxide;

[0024] The solid powder in the light yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 2.0 parts of zinc oxide, and 1.0 parts of antimony oxide;

[0025] The solid powder in the printing ink used in the blue UV ink is composed of the following components by weight: 100 parts of glaze powder, 3.0 parts of cobalt oxide, 1.5 parts of silicon dioxide, and 0.5 parts of magnesium oxide;

[0026] The solid powder in the printing ink used in the orange UV ink is composed of the following components by mass: 100 parts of glaze powder, 4.0 parts of zirconium dioxide, 2.5 parts of ferric oxide, and 1.0 part of manganese oxide.

[0027] Preferably, in step S7, the resolution of UV ink printing is 100-360dpi, and the number of printing layers is 1-2 layers.

[0028] Another aspect of the present invention also provides colorful light-transmitting ceramic tiles prepared by the above-mentioned preparation process.

[0029] The beneficial effects of this application are:

[0030] The ceramic tile of the present application optimizes the ceramic tile structure and combines the fixed colored grains with different levels of pattern layers, glaze layers, etc. through a multi-level design to simulate the texture, pattern and visual effect of natural colored flower stone. Furthermore, the present application also optimizes the ceramic tile preparation process, three-dimensional scanning, and layered printing, especially the reverse positioning printing pattern at the bottom of the ceramic tile to improve the color level and three-dimensional sense. The obtained ceramic tile can not only achieve accurate color transparency and natural gradient, but also build a delicate sense of hierarchy and rich optical effects on the ceramic tile surface. Not only does it avoid the repetition of patterns and the singleness of colors, but it also gives the ceramic tile a realistic three-dimensional sense and light transmittance, making it stand out among high-end decorative materials, and truly achieving an artistic effect comparable to natural colored flower stone. Furthermore, combined with process optimization, the production process is simplified, and the printed pattern is not easy to fall off and has a good color. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a picture showing the effect of the ceramic tile under a light tube according to an embodiment of the present invention;

[0032] Figure 2 The original stone image scanned by the embodiment of the present invention;

[0033] Figure 3 This is a schematic diagram of a pattern printed on the bottom of a tile according to an embodiment of the present invention;

[0034] Figure 4 The following is an explanation of the grading standard for the ink coating adhesion test according to an embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0036] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0038] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0039] The present application provides a three-dimensional multi-dimensional colorful translucent ceramic tile, comprising a colorful rough blank, on the surface of which a pattern layer, a colored grain layer, and a transparent protective glaze layer are arranged in sequence from bottom to top, and a positioning printing layer is provided on the bottom surface of the blank; the colorful rough blank is formed by pressing a translucent blank and a translucent colorant through a concave and convex mold; the colored grain layer is distributed on the colorful part of the ceramic tile.

[0040] Specifically, the multi-color rough blank can be made of conventional light-transmitting blanks and light-transmitting colorants. Preferably, the overall light transmittance of the light-transmitting blanks and colorants is ≥5%. The colorants are wrapped colorants, which can be formed by adding corresponding color powders to the light-transmitting blanks. The prepared light-transmitting blanks and light-transmitting colorants can be partially distributed into the color parts by the method of partial distribution according to the color of the designed color flowers, and further filled with light-transmitting blanks, and the preparation of the multi-color rough blank layer is completed by pressing.

[0041] The toner can be selected from commonly used toners according to different colors. The toner can be one or more of the commonly used colorants of red, blue, brown, yellow, black, and green.

[0042] The color of the rough blank is usually to simulate the base color of a large area, and can be prepared by referring to the method of existing colored transparent tiles. It can be achieved by combining different blanks and color powders, and flashing dry particles can also be added to achieve better visual effects. For example, in a specific embodiment, the rough blank raw materials include black dry particles, gray dry particles, flashing dry particles, and white dry particles.

[0043] The pattern layer is a basic texture or pattern, which is usually formed by inkjet printing.

[0044] The colored grain layer is mainly distributed in the colored flower area. The optical effect is formed through the polycrystalline effect of the colored grains and the pattern of the blank and the pattern layer. It is more three-dimensional and changeable, thereby better simulating the colored flower effect of natural colored flower stone.

[0045] The colored flowers can be red, rose, green, yellow, etc., and different colored grain layers can be arranged according to the simulated colors. By separately designing the colored grain layer to simulate the colored flowers, combined with the transparent glaze layer, etc., the defect of heavy color of the material is solved, and the surface of the tile is given the effect of the jade ice interface of marble tiles, which deeply restores the visual three-dimensional sense and transparency of the colored marble.

[0046] The protective glaze layer mainly plays a protective role, and through different refractions and combined with the concave and convex effects, it forms a sense of layering and transparency. Conventional tile protective glaze can be used.

[0047] The positioning printing layer is placed at the bottom of the blank to further increase the layering and light and dark effects. It can be formed by UV ink, which cures quickly and has rich colors, achieving accurate color matching and gradient effects, and further enhancing the light and dark difference to achieve a sense of stone transparency.

[0048] The preparation process of the three-dimensional multi-dimensional colored light-transmitting ceramic tile of the present invention comprises the following steps:

[0049] S1: Scan the stone and make a concave and convex mold.

[0050] By scanning the stone and using the grayscale image, a concave and convex mold is made. Preferably, the three-dimensional effect of the colored flower part can be established by light and dark processing for extraction, thereby enhancing the three-dimensional sense of the flower body.

[0051] S2: Use a concave-convex mold to press the light-transmitting blank and the light-transmitting colorant to form a colorful rough blank.

[0052] Conventional transparent blanks and transparent colorants are selected. Preferably, the overall light transmittance of the transparent blanks and colorants is ≥5%. The colorants are wrapped colorants, which can be formed by adding corresponding color powders to transparent blanks. The prepared transparent blanks and transparent colorants can be partially distributed into the color parts by the method of partial distribution according to the color of the designed color flowers, and further filled with transparent blanks, and the preparation of the multi-color rough embryo layer is completed through pressing.

[0053] S3: Drying, printing a decorative pattern on the surface of the dried blank to form a pattern layer.

[0054] S4: adding colored crystal grains locally on the surface of the blank obtained in step S3, wherein the colored crystal grains correspond to the colored patterned parts of the blank.

[0055] Preferably, in step S4, colored grain wet glaze can be prepared and colored grains can be locally added to the surface of the blank by screen printing, so that the positioning is more precise and the amount of glazing of the grains can be better controlled so as to facilitate the control in combination with the thickness of the concave and convex texture of the tile, so that the final three-dimensional effect of the tile surface is better.

[0056] S5: spraying dry granular protective glaze on the surface of the body obtained in step S4.

[0057] Protective glaze can be commonly used as glaze for transparent tiles.

[0058] S6: Firing and polishing.

[0059] S7: Process the bottom of the tile obtained in step S6, and print the decorative pattern described in step S3 on the bottom of the tile in reverse positioning.

[0060] In the traditional ceramic tile process, only the surface of the ceramic tile is treated. The present application scheme processes the back of the ceramic tile, utilizes the light transmittance of the translucent body, and prints the decorative pattern in reverse positioning on the bottom of the ceramic tile, which echoes the pattern layer on the surface of the body. This can give the colorful ceramic tile an optical color contrast, and highlight the brightness and color impact of the colorful part as well as the light transmittance.

[0061] Wherein, the bottom of the tile is treated by cleaning only the surface of the tile to ensure that the bottom is clean and convenient for printing patterns. In addition, in order to further improve the bonding force, the bottom of the tile may also be pre-treated (such as roughening or adding a bonding coating) and then the inkjet printing process is performed, so that the printed layer and the tile are more firmly bonded. Preferably, the bottom of the tile is surface plasma cleaned, and then a nano-silicon dioxide layer is set. The performance of the tile surface can be significantly improved by the dual effects of chemical bonding and physical filling of the nano-silicon dioxide layer. The high specific surface area and surface activity of nano-silicon dioxide enable it to interact strongly with tiles and ink molecules, including forming chemical bonds such as covalent bonds and hydrogen bonds, and also through physical adsorption such as van der Waals forces. These interactions not only enhance the adhesion between the ink and the tile, but also improve the surface flatness by filling the tiny pores on the surface. Therefore, the application of the coating not only improves the wear resistance and scratch resistance of the bottom ink, but also ensures the durability and color stability of the UV ink printing pattern. The formation of the nano-silicon dioxide layer can be formed by coating a silane coupling agent and then curing after heating, or it can be directly coated with a nano-silicon dioxide slurry.

[0062] Preferably, advanced UV-curable ink deposition technology is used to customize the color pattern of the bottom of the treated tile with high precision and selectivity. It can be cured quickly and has rich colors, achieving precise color matching and gradient effects, and further enhancing the light and dark difference to achieve a sense of transparency in the stone.

[0063] UV printing ink may contain printing ink and solid powder, the solid powder includes color powder and glaze powder, in some preferred embodiments, the chemical composition of the glaze powder, in terms of oxide mass percentage, includes: SiO2 45-50%, Al2O3 18-23%, CaO 8-13%, MgO 2-3.5%, K2O 0.5-1%, Na2O 4-5%, BaO 0.3-0.5%, ZnO 2-3% and the remainder of ignition loss.

[0064] The UV printing ink may be UV ink commonly used for printing on glass or ceramics.

[0065] In some preferred embodiments, the solid powder in the rose red UV ink is composed of the following components by mass: 100 parts of glaze powder, 1.5 parts of chromium oxide, 4.0 parts of tin oxide, 1.2 parts of ferric oxide, and 0.3 parts of cobalt oxide.

[0066] In some preferred embodiments, the solid powder in the pink UV ink is composed of the following components by mass: 100 parts of glaze powder, 5.0 parts of tin oxide, 2.5 parts of spodumene, 0.2 parts of cobalt oxide, and 1.0 parts of aluminum oxide.

[0067] In some preferred embodiments, the solid matter in the yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 3.0 parts of cerium oxide, and 0.8 parts of ferric oxide.

[0068] In some preferred embodiments, the solid powder in the light yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 2.0 parts of zinc oxide, and 1.0 parts of antimony oxide.

[0069] In some preferred embodiments, the solid powder in the blue printing ink is composed of the following components by mass: 100 parts of glaze powder, 3.0 parts of cobalt oxide, 1.5 parts of silicon dioxide, and 0.5 parts of magnesium oxide.

[0070] In some preferred embodiments, the solid powder in the printing ink used for orange is composed of the following components by mass: 100 parts of glaze powder, 4.0 parts of zirconium dioxide, 2.5 parts of ferric oxide, and 1.0 part of manganese oxide.

[0071] The following is further described in conjunction with specific embodiments.

[0072] Example 1

[0073] This embodiment mainly completes the firing of semi-finished ceramic tiles and selects the better rough blank raw materials, which specifically includes the following steps:

[0074] S1: Scan the stone and make a concave and convex mold.

[0075] By scanning the stone, using grayscale images (such as Figure 2 As shown in the figure, a concave and convex mold is made. The three-dimensional effect of the colored flower part is established through light and dark processing, and then extracted to further enhance the three-dimensional sense of the flower body.

[0076] S2: Use a concave-convex mold to press the light-transmitting blank and the light-transmitting colorant to form a colorful rough blank.

[0077] The colorful rough raw material composition includes black dry particles, gray dry particles, flashing dry particles, and white dry particles. By setting different proportions, the embodiments 1-1 to 5 are distributed and set to select the best effect.

[0078] S3: Drying, printing a decorative pattern on the surface of the dried blank to form a pattern layer.

[0079] S4: Colored grains are locally added to the surface of the blank obtained in step S3, and the colored grains correspond to the colored patterned parts of the blank.

[0080] Rose red grains are selected, and their chemical composition, in terms of oxide mass percentage, includes: 43.9% silicon dioxide, 8.94% aluminum oxide, 1.41% iron oxide, 8.17% calcium oxide, 2.18% magnesium oxide, 1.82% potassium oxide, 0.4% sodium oxide, 0.08% titanium dioxide, 0.97% manganese oxide, 0.2% phosphorus pentoxide, 0.15% hafnium dioxide, 1.53% barium oxide, 1.45% zinc oxide, 27.7% zirconium dioxide, 0.01% strontium oxide, 0.05% lead oxide, 0.01% nickel oxide, 0.27% chromium oxide, 0.35% cobalt oxide, and the remainder on ignition.

[0081] S5: spraying dry granular protective glaze on the surface of the body obtained in step S4.

[0082] The specific gravity of the protective glaze is 1.45, the glaze amount is 50-60g, and its chemical composition, calculated by mass percentage of oxides, includes: 46.03% silicon dioxide, 16.48% aluminum oxide, 0.13% iron oxide, 5.53% calcium oxide, 0.45% magnesium oxide, 2.83% potassium oxide, 3.35% sodium oxide, 0.12% titanium dioxide, 0.05% phosphorus pentoxide, 0.09% sulfur trioxide, 14.16% barium oxide, 4.7% zinc oxide, 0.09% zirconium dioxide, 2.99% strontium oxide, 0.02% lead oxide, and the remainder by ignition loss.

[0083] S6: Firing and polishing.

[0084] Sintered at about 1215℃, with a firing cycle of 65 minutes, and then polished.

[0085] Table 1 shows the sample formulas of Examples 1-1 to 5 and the final sintering effect statistics. It can be seen that 1-1 has the best effect.

[0086] Table 1 Formulas and effect statistics of each experimental example in Example 1

[0087]

[0088] The following Examples 2-4 further process the bottom of the tile on the basis of Example 1, and print the decorative pattern in step S3 in a single layer in reverse positioning to obtain the three-dimensional multi-dimensional colorful flower translucent tile of the embodiment of the present invention. By gradually optimizing the processing conditions and testing the performance of the printing layer, the better conditions are selected.

[0089] Performance characterization methods used in the experiment:

[0090] (1) After UV ink coating, the color is transmitted through the glossiness. The three-dimensional imitation rain flower stone tiles are placed on the light box, and the glossiness of the tiles to be tested is measured and determined, and compared with the glossiness of the original stone under sunlight. When the color gloss similarity of the two differs by <10°, it is considered to be very similar to the original stone.

[0091] (2) UV ink coating adhesion test, the coating adhesion is tested by the cross-cut method (refer to GB / T 9286-2021 paint and varnish cross-cut test), and the loose film in the cut area is removed by manual cutting. The center of the tape is placed on the grid, parallel to the cutting line, covering the grid area and flattening it. After 5 minutes, hold the tape in the air for a while, and at an angle as close to 60° as possible, tear it off smoothly within 0.5 s to 1.0 s, and visually evaluate whether there is any potential residue of the substrate on the back of the tape. The test result classification standard is as follows: Figure 4 shown.

[0092] Example 2

[0093] According to the results of Example 1, the best condition 1-1 is selected as the basis to further optimize the processing process of the bottom tiles in step S7.

[0094] Step S1-6 can refer to Example 1-1. Specifically, step S7 is as follows: the bottom of the tile obtained in step S6 is cleaned in different ways, and the same decorative pattern in step S3 is printed on the bottom of the tile in reverse positioning. The details are shown in the following table.

[0095] Table 2 Parameters of each experimental example in Example 2

[0096] Serial number Brick bottom treatment process Example 2-1 Sweep the bottom Example 2-2 Grinding and polishing Example 2-3 Grinding and polishing cleaning + surface coating treatment Embodiment 2-4 Surface plasma cleaning + silane coupling agent

[0097] The specific parameters involved are as follows:

[0098] Sweep the bottom, use a sweeper to clean the bottom surface of the tile, and then perform UV printing;

[0099] Grinding and polishing cleaning: use a 240 mesh diamond brush and a 240 mesh fiber brush to clean the bottom of the brick, and then perform UV printing;

[0100] Grinding and polishing cleaning + surface coating treatment: After the bottom is treated with the grinding and polishing cleaning used in Example 1-2, an acrylic primer is applied to the bottom of the tile, and then UV printing is performed.

[0101] Surface plasma cleaning + silane coupling agent, after treating the bottom of the tile with plasma treatment for 10 minutes, apply silane coupling agent on the bottom of the tile, bake to form a nano-silicon dioxide coating, and finally perform UV ink printing.

[0102] After the bottom of the tile is processed, UV ink is printed in a positioning manner, and the pattern is the same as the decorative pattern in step S3. The UV ink formula is: printing oil, glaze powder, and color powder, wherein the glaze powder includes, by oxide mass percentage: SiO2 48.94%, Al2O3 20.30%, CaO 10.76%, MgO 2.96%, K2O 0.69%, Na2O 4.97%, BaO 0.42%, ZnO 2.44% and ignition loss 8.52%.

[0103] The solid powder in the rose red UV ink is composed of the following components by mass: 100 parts of glaze powder, 1.5 parts of chromium oxide, 4.0 parts of tin oxide, 1.2 parts of ferric oxide, and 0.3 parts of cobalt oxide.

[0104] The solid powder in the pink flower UV ink is composed of the following components by mass: 100 parts of glaze powder, 5.0 parts of tin oxide, 2.5 parts of spodumene, 0.2 parts of cobalt oxide, and 1.0 parts of aluminum oxide.

[0105] The solid matter in the yellow flower UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 3.0 parts of cerium oxide, and 0.8 parts of ferric oxide.

[0106] The solid powder in the light yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 2.0 parts of zinc oxide, and 1.0 parts of antimony oxide.

[0107] The solid powder in the printing ink used for blue flowers is composed of the following components by mass: 100 parts of glaze powder, 3.0 parts of cobalt oxide, 1.5 parts of silicon dioxide, and 0.5 parts of magnesium oxide.

[0108] The solid powder in the printing ink used for the orange flower consists of the following components by mass: 100 parts of glaze powder, 4.0 parts of zirconium dioxide, 2.5 parts of ferric oxide, and 1.0 part of manganese oxide.

[0109] The resolution of UV ink printing is 300dpi and the number of printing layers is 1.

[0110] After curing, the bonding strength of the positioning printing layer of each sample was measured, and the results are shown in the following table:

[0111] Table 3 Example 2 Sample Printing Strength Test Results

[0112]

[0113]

[0114] The cross-hatch method was used to test the effects of different treatment processes on the adhesion of UV ink on the bottom of the ceramic tile, and the adhesion level between the UV ink and the bottom of the ceramic tile after each treatment was evaluated. According to the data in the table, the treatment process of the bottom of the ceramic tile is crucial to the adhesion performance of the UV ink. After the cross-hatch test, the UV ink in Example 2-1 almost completely fell off, showing the worst adhesion. In Example 2-2, the UV ink fell off in a large area along the scratches, which could not meet the daily product use requirements; in Example 2-3, the UV ink fell off in the scratches. The area is less than 15%, which basically meets the use requirements; in Example 2-4, the UV ink fell off in an area of ​​only 2%, showing the best adhesion performance.

[0115] Example 3

[0116] According to the results of Example 2, the printing resolution is further optimized.

[0117] The raw materials and specific preparation steps are all referred to Example 1-1, the brick bottom and back treatment process steps are referred to Example 2-4, and the specific printing parameters involved in the steps are shown in Table 4. By using parameters of different resolutions, the content of UV ink attached to the surface is controlled.

[0118] Table 4 Parameters of Example 3

[0119] Serial number UV ink printing resolution (dpi) Example 3-1 60 Example 3-2 300 Example 3-3 400

[0120] The performance tests of Example 3-1 to Example 3-3 were carried out, and the results are shown in the following table:

[0121] Table 5 Example 3 sample printing light measurement, adhesion test results

[0122]

[0123]

[0124] The above table shows the results of the gloss similarity of UV ink printed at different resolutions to the original stone and the bonding performance of UV ink to the tile base. In terms of visual similarity, Example 3-1, at a resolution of 60dpi, the gloss of UV ink printing is low, and the similarity is poor compared to the original stone (gloss difference ≥15°). Example 3-2, at a resolution of 300 dpi, the gloss of UV ink printing is closer to the target value, and the difference in similarity with the gloss of natural stone is less than 5°, achieving the ideal effect. Example 3-3, at a resolution of 400 dpi, the similarity is similar to Example 3-2, and the difference in similarity with the gloss of natural stone is less than 8°, but it is not significantly better than the effect of 300 dpi.

[0125] From the application performance point of view, in Example 3-1, the UV ink has a large shedding area (<15%), and the adhesion performance is poor. In Example 3-2, the UV ink has almost no shedding, and the shedding area is less than 2%, showing the best adhesion. In contrast, the UV ink shedding area of ​​Example 3-3 is similar to that of Example 3-1, which is still large, and the adhesion is not significantly improved.

[0126] In summary, UV ink printing at a resolution of 300 dpi shows the best gloss, similarity and adhesion, proving that 300 dpi is the optimal printing resolution.

[0127] Example 4

[0128] According to the results of Example 3, the printing parameters are further optimized.

[0129] The raw materials and specific preparation steps are all referred to Example 1-1, the brick bottom and back treatment process steps are referred to Example 2-4, and the UV ink printing resolution is referred to Example 3-2. The specific printing parameters involved in the steps are shown in Table 6. Parameters of different thicknesses are used to control the content of UV ink attached to the surface and adjust the printing effect.

[0130] Table 6 Parameter adjustment description of Example 4

[0131] Serial number UV printing layers Example 4-1 1 Example 4-2 3

[0132] The performance test of Example 4-1 to Example 4-2 was carried out, and the results are as follows:

[0133] Table 7 Example 4 Sample Test Results

[0134]

[0135]

[0136] The above table shows the gloss similarity of UV ink printed at different thicknesses to the original stone and the bonding performance of UV ink to the tile bottom. In terms of gloss, in Example 4-1 (single-layer printing), the gloss of each color is generally good, and the difference in similarity to the gloss of natural stone is less than 5°, indicating that single-layer printing has reached a higher gloss level. In Example 4-2 (three-layer printing), the gloss is further improved, especially in pink, yellow and orange, the improvement is obvious, but not all colors are significantly improved. In terms of similarity, the gloss of Example 4-1 is very close to the original stone. The similarity of Example 4-2 is slightly improved, but the similarity of some colors (such as light yellow) is not significantly improved, and there is no significant difference from Example 4-1. In terms of adhesion, Example 4-1 has better adhesion, and Example 4-2 has a surface shedding area of ​​almost 25%, which does not meet the use requirements.

[0137] According to experimental data, although three-layer printing (Example 4-2) improves the glossiness of some colors, it has little effect on the similarity and adhesion of most colors. In contrast, single-layer printing (Example 3-1) achieves a better balance between glossiness, similarity and adhesion, with a glossiness close to that of the original stone and excellent adhesion. Therefore, printing 1 to 2 layers is more appropriate. Figure 1 This is the effect picture of the three-dimensional multi-dimensional colorful light-transmitting ceramic tile obtained in Example 4-2 under the light tube. Figure 3 Schematic diagram of the printed pattern on the bottom of the tile of Example 4-2.

[0138] The raw materials or reagents used in the examples and comparative examples of the present invention are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or concentration are all analytically pure raw materials or reagents that can be routinely obtained. As long as they can play the expected role, there is no special limitation.

[0139] The instruments and equipment used in this embodiment are all purchased from major manufacturers in the market, and there is no particular limitation as long as they can play the expected role. In this embodiment, if no specific technology or conditions are specified, the technology or conditions described in the literature in this field or the product instructions are used. The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A three-dimensional multi-dimensional colorful translucent ceramic tile, comprising a colorful rough blank, the surface of which is provided with a pattern layer, a colored grain layer, and a protective glaze layer in sequence from bottom to top, and a positioning printing layer is provided on the bottom surface of the blank; the colorful rough blank is formed by pressing a translucent blank and a translucent colorant through a concave-convex mold; the colored grain layer is distributed in the colorful part of the ceramic tile.

2. The process for preparing ceramic tiles according to claim 1, characterized in that: Includes steps: S1: Scan the stone and make a concave and convex mold; S2: Using a concave-convex mold, the light-transmitting blank and the light-transmitting colorant are pressed to form a colorful rough blank; S3: drying, printing a decorative pattern on the surface of the dried blank to form a pattern layer; S4: adding colored grains locally on the surface of the blank obtained in step S3, wherein the colored grains correspond to the colored patterned parts of the blank; S5: spraying dry granular protective glaze on the surface of the body obtained in step S4; S6: Firing and polishing; S7: Process the bottom of the tile obtained in step S6, and then print the decorative pattern described in step S3 on the bottom of the tile in reverse positioning.

3. The preparation process according to claim 2, characterized in that: In the step S1, the three-dimensional effect of the colorful flower part is scanned and extracted through light and shade processing.

4. The preparation process according to claim 2, characterized in that: In the step S2, the overall light transmittance of the light-transmitting blank and the colorant is ≥5%, and the colorant is a wrapped colorant.

5. The preparation process according to claim 2, characterized in that: In the step S4, colored grains are locally added to the surface of the blank by screen printing.

6. The preparation process according to claim 2, characterized in that: In the step S7, processing the bottom of the tile includes: plasma cleaning the surface of the bottom of the tile, and then providing a nano-silicon dioxide coating.

7. The preparation process according to claim 2, characterized in that: In the step S7, a pattern is printed on the bottom of the treated tile using UV ink.

8. The preparation process according to claim 7, characterized in that: In step S7, the UV printing ink comprises printing ink and solid powder, the solid powder comprises toner and glaze powder, and the chemical composition of the glaze powder comprises, in terms of oxide mass percentage: SiO2 45-50%, Al2O3 18-23%, CaO 8-13%, MgO 2-3.5%, K2O 0.5-1%, Na2O 4-5%, BaO 0.3-0.5%, ZnO 2-3% and the remainder by ignition loss.

9. The preparation process according to claim 8, characterized in that: In step S7, the solid powder in the rose red UV ink is composed of the following components by mass: 100 parts of glaze powder, 1.5 parts of chromium oxide, 4.0 parts of tin oxide, 1.2 parts of ferric oxide, and 0.3 parts of cobalt oxide; The solid powder in the pink UV ink is composed of the following components by mass: 100 parts of glaze powder, 5.0 parts of tin oxide, 2.5 parts of spodumene, 0.2 parts of cobalt oxide, and 1.0 parts of aluminum oxide; The solid matter in the yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 3.0 parts of cerium oxide, and 0.8 parts of ferric oxide; The solid powder in the light yellow UV ink is composed of the following components by mass: 100 parts of glaze powder, 6.5 parts of titanium dioxide, 2.0 parts of zinc oxide, and 1.0 parts of antimony oxide; The solid powder in the blue ink is composed of the following components by weight: 100 parts of glaze powder, 3.0 parts of cobalt oxide, 1.5 parts of silicon dioxide, and 0.5 parts of magnesium oxide; The solid powder in the printing ink used for orange is composed of the following components by mass: 100 parts of glaze powder, 4.0 parts of zirconium dioxide, 2.5 parts of ferric oxide, and 1.0 part of manganese oxide.

10. The preparation process according to claim 9, characterized in that: In step S7, the resolution of UV ink printing is 100-360dpi, and the number of printing layers is 1-2 layers.

Citation Information

Cited By

  • Thangka preparation method combined with porcelain painting process

    CN120289209A